(untitled) (Revista Brasileira Multidisciplinar, 2010)
Piumhi river was a tributary of Grande river until the late 50s. The Furnas reservoir construction has reversed Piumhi river to São Francisco river through a canal and a dam in Capitólio city (MG). The aim of this study was to record the perception that local people had on the river Piumhi transposition by means of newspapers, books, documents and interviews using the life history technique. Different perceptions were evident in the interviews, depending on the geographic region where the subjects lived. In Capitólio, besides the dike, the most striking fact was the flooding of the Furnas reservoir, affecting the rural area. Between Capitólio and the beginning of rural Piumhi, where the transposition channels are, the most striking fact was the change of the riverbed and the floodplain. Near the town of Piumhi, where there was a marsh that reached to the urban zone, the drainage of the flooded area transformed into arable land caused land conflicts. The record of the population’s perception demonstrates social conflicts, economic and environmental impacts generated by the change in the landscape, recording how people felt and dealt with the facts in their lives.